EFFECT OF MORINGA LEAVES EXTRACT, CALCIUM, AND POTASSIUM SILICATE ON THE GROWTH, YIELD, AND QUALITY OF STRAWBERRY FRUITS - Rasha Raad Mohammed; Bayan Hamza Majeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
A field and storage experiments were carried out in order to evaluate the effect of the foliar application of Moringa leaves extract, calcium, and potassium silicate on the growth, yield, and quality characteristics of strawberry fruits. The field experiment with three replicates was included 27 treatments consisted of the foliar application of Moringa leaf extract at the concentrations of 0, 5, and 10% which were symbolized as M0, M1, and M2 respectively, calcium at the concentrations of 0, 1, and 2 g. L-1, which were symbolized as Ca0, Ca1, and Ca2 respectively, and potassium silicate at the concentrations of 0, 1.25, and 2.50 ml. L-1 that symbolized as S0, S1, and S2 respectively. The storage experiment was carried out according to the same design that applied in the first experiment, at a temperature of 0-2ºC. The results revealed that the M2 treatment was significantly increased the leaves content of chlorophyll, Leaves area, shoots dry weight, flowers number, the fruit set percent and number, leaves and fruits content of calcium, fruits firmness, and it also reduced the damage percent and the weight loss. While the treatment of Ca1 recorded the most significant values of growth and yield indicators, and the lowest damage percent and weight loss. Also, the Ca2 treatment recorded the highest leaves and fruits content of calcium, and firmness. S2 also recorded the highest values in the above indicators. The interaction treatments revealed significant values in the above-mentioned indicators, as the interactions of M2Ca1, M2S2, and Ca1S2 and the triple interaction of M2Ca1S2 were recorded the highest values compared to the control treatments.